2020
DOI: 10.1186/s13104-020-04973-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Leishmania RNA Virus (LRV) and treatment failure in clinical isolates of Leishmania major

Abstract: Objective: Leishmaniasis is caused by different Leishmania spp. Treatment failure (TF) of cutaneous leishmaniasis (CL) is a serious issue that may be due to various reasons, previous studies suggested Leishmania RNA virus (LRV) as a potential cause of TF. Two variant groups of LRV1 and LRV2 are reported. In this study, the presence of LRV1/LRV2 was compared in TF with treatment response (TR) isolates of L. major. Clinical isolates of 15 TF and 15 TR were collected from CL patients referred to the Health Center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Although Leishmaniavirus has been detected at lower frequency in Old World L. major strains 59,60 , there is no conclusive data to suggest an involvement in pathogenesis and treatment failure. In Iranian cases, L. major infection was not influenced by the presence or absence of LRV2 61 . In any event, both L. major MRC-01 and L. major MRC-02 were demonstrated to be negative for LRV2.…”
Section: Discussionmentioning
confidence: 82%
“…Although Leishmaniavirus has been detected at lower frequency in Old World L. major strains 59,60 , there is no conclusive data to suggest an involvement in pathogenesis and treatment failure. In Iranian cases, L. major infection was not influenced by the presence or absence of LRV2 61 . In any event, both L. major MRC-01 and L. major MRC-02 were demonstrated to be negative for LRV2.…”
Section: Discussionmentioning
confidence: 82%
“…Also, LRV-1 was significantly associated with a high risk of treatment failure in L. braziliensis patients of Peru and Bolivia (Adaui et al, 2016). Although Abtahi et al (2020) showed no LRV-1 in any of the L. major treatment failure (TF) samples, seven treatment responsive (TR) isolates and two TF isolates were positive for LRV-2, that no significant difference was identified among LRV-2 and response to Glucantime R .…”
Section: Leishmania Rna Virusmentioning
confidence: 97%
“…It has been mentioned that LRV can be proposed as a potential cause of treatment failure (TF) in CL (Abtahi et al, 2020), as in L. guyanensis infection, all patients infected with LRV1-negative L. guyanensis were treated after one or two doses of pentamidine, but 27.3% of LRV1-positive patients represented persistent infection and symptomatic relapse that needed additional treatment or using of second-line drugs (Bourreau et al, 2015).…”
Section: Leishmania Rna Virusmentioning
confidence: 99%
“…Although Leishmaniavirus has been detected at lower frequency in Old World L. major strains 55,56 , there is no conclusive data to suggest an involvement in pathogenesis and treatment failure. In Iranian cases, L. major infection was not influenced by the presence or absence of LRV2 57 . In any event, both L. major _MRC-01 and L. major _MRC-02 were demonstrated to be negative for LRV2.…”
Section: Discussionmentioning
confidence: 82%